2005
DOI: 10.1590/s1413-73722005000300002
|View full text |Cite
|
Sign up to set email alerts
|

Trabalho de casa, tarefas escolares, auto-regulação e envolvimento parental

Abstract: RESUMO. Urge entender o Trabalho de Casa (TPC) como processo complexo para o qual conflui um vasto leque de factores impactantes. Neste relato analisam-se as relações entre os perfis de atitudes e comportamentos diante do TPC de Inglês e o nível instrutivo dos pais, a auto-eficácia percebida nessa disciplina bem como a correlação entre tais perfis de TPC e os perfis auto-regulatórios, em face do estudo. A amostra tomada é composta de 3929 alunos. O nível instrutivo dos pais associa-se positiva e significativam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
14

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 30 publications
0
27
0
14
Order By: Relevance
“…Estos estudiantes manifi estan, aunque no siempre son totalmente conscientes de ello, una teoría personal sobre el estudio que les permite mantener en su actividad diaria una conducta de estudio bien ajustada, conducta que parecen haber desarrollado por sí solos sin que nadie se haya dedicado a enseñarles las formas efi caces para estudiar (Rosário, Mourão, Soares, Chaleta, Grácio, Núnez & González-Pienda, 2005;Zimmerman, 2002).…”
unclassified
“…Estos estudiantes manifi estan, aunque no siempre son totalmente conscientes de ello, una teoría personal sobre el estudio que les permite mantener en su actividad diaria una conducta de estudio bien ajustada, conducta que parecen haber desarrollado por sí solos sin que nadie se haya dedicado a enseñarles las formas efi caces para estudiar (Rosário, Mourão, Soares, Chaleta, Grácio, Núnez & González-Pienda, 2005;Zimmerman, 2002).…”
unclassified
“…Elementary school students had higher results in planning when compared with middle school students. This result may reflect the progressive decreasing in the involvement in the studying activities and in the positive attitudes towards homework as the students advance in the educational system (Rosário et al, 2005). Hong et al (2009) had also found that students from the 11th grade planned homework less than the 7th grade students.…”
Section: Discussionmentioning
confidence: 98%
“…Teachers have a determining role for the final quality of the work performed [23]. The figure of the teacher as mediator, at the Sesi/PR proposal, comes precisely to mediate the process between creating their own action mechanisms and responding to the challenge.…”
Section: Facing the Challenge: The Cycle Of Problem-solving By Adolesmentioning
confidence: 99%
“…It demands regulatory and self-regulatory efforts committed to learning. According to Rosário [23], self-regulating students of their learning see the events in school as opportunities to expand their experiences, valuing them. This becomes important insofar as these experiences lived and worked through strategies and can support the others that will come after the school period.…”
Section: The Team Facing the Challenge: Obstacles And The Expert's Romentioning
confidence: 99%